Análise de dados e experimentos na administração de negócios - Bastos, Milton Briguet (2001)
This study focuses on the data and experiment analysis. lt will help us to understand the use of data and experimental analysis on several business administration practices including: Decision and Risk Analysis, Business Process Reengineering, Six Sigma and Taguchi Quality Systems. It also discusses thinking methods and its implementation, illustrated by examples. In addition, the study also covers the use of those analyses to develop Business Intelligence within the organization.